2020
DOI: 10.1016/j.bja.2020.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Individualised positive end-expiratory pressure guided by electrical impedance tomography for robot-assisted laparoscopic radical prostatectomy: a prospective, randomised controlled clinical trial

Abstract: Background: Robot-assisted laparoscopic radical prostatectomy requires general anaesthesia, extreme Trendelenburg positioning and capnoperitoneum. Together these promote impaired pulmonary gas exchange caused by atelectasis and may contribute to postoperative pulmonary complications. In morbidly obese patients, a recruitment manoeuvre (RM) followed by individualised PEEP improves intraoperative oxygenation and end-expiratory lung volume (EELV). We hypothesised that individualised PEEP with initial RM similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(91 citation statements)
references
References 21 publications
6
85
0
Order By: Relevance
“…Furthermore, our results cannot be fully transferred to other patient populations or to laparoscopic procedures with different patient positioning, even if a recent publication found that comparable individualized PEEP values are necessary in normal-weight patients undergoing laparoscopic surgery in extreme Trendelenburg positioning. 32 Our study was neither designed nor powered to investigate the impact of an individualized PEEP strategy on the incidence of postoperative pulmonary complications. Considering the slightly higher rate of hemodynamic complications and the time needed for the PEEP titration, we strongly encourage (1) testing whether an individualized PEEP strategy also translates into a lower rate of postoperative pulmonary complications, and (2) searching for alternative methods for individualization of mechanical ventilation that would be more applicable in clinical routine.…”
Section: Limitationsmentioning
confidence: 99%
“…Furthermore, our results cannot be fully transferred to other patient populations or to laparoscopic procedures with different patient positioning, even if a recent publication found that comparable individualized PEEP values are necessary in normal-weight patients undergoing laparoscopic surgery in extreme Trendelenburg positioning. 32 Our study was neither designed nor powered to investigate the impact of an individualized PEEP strategy on the incidence of postoperative pulmonary complications. Considering the slightly higher rate of hemodynamic complications and the time needed for the PEEP titration, we strongly encourage (1) testing whether an individualized PEEP strategy also translates into a lower rate of postoperative pulmonary complications, and (2) searching for alternative methods for individualization of mechanical ventilation that would be more applicable in clinical routine.…”
Section: Limitationsmentioning
confidence: 99%
“…Similar questions need to be answered for other EITbased parameters, such as the global inhomogeneity (GI) index (20) and regional ventilation delay (RVD) (21), to assess the spatial and temporal ventilation distribution. The GI and RVD were proposed to guide PEEP optimization (4,22) and weaning from ventilation (23). Standard reference values for these parameters may aid in the clinical application of EIT.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequately low PEEP values during laparoscopic surgery (in STP) favor the development of atelectasis and decreases pulmonary ventilation and oxygenation. Two current studies using electrical impedance tomography during RALP shows that a PEEP with 14 to 15 cmH 2 O improves oxygenation in non-obese individuals [32,33].…”
Section: Perioperative Ventilation and Blood Oxygenationmentioning
confidence: 99%